The value and elements of Malay culture as content in modern Malaysian painting / Siti Humaini Syed Ahmad - Syed Ahmad, Siti Humaini (2015)
In modem Malaysian paintings, form and meaning to artwork produced by young artist are believed to be detached from Malay cultural heritage. Young artists who have the attitude of putting the Western art first are greatly regrettable. Therefore, it is imperative for researchers to carry out detailed studies on the importance of values and elements of Malay culture in modem Malaysian paintings. The objective of this research is to identify the values and the elements of Malay culture as content in modem Malaysian painting by local artists from 1970s to 1990s. Art practitioners’ view and case study was applied in this research in order to obtain the data. A total 22 respondents were interviewed and 15 paintings were chosen to be analyzed. The finding from this research shows that Malay cultural values in modem painting comprise of the value of finesse in Malay culture, the value of the identity and value of the Malay culture in the global aspect. Malay cultural values in modem painting also able to uphold racial culture, practise positive values in Malay culture and portrays modem Malaysian art identity. Therefore, the outcome of this research could be related to the suggestions in developing modem Malaysian paintings which revolve around the theme of Malay cultural values.